2 Utilization of Liquid Fertilizer from Seaweed (Sargassum 3 spp) On the growth of Shallots (Allium cepa) - Sabrina, Dinda; Razak, Abdul (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Shallots (Allium cepa L) is one type of superior vegetable that has long been cultivated by farmers. The demand and need for shallots that continue to increase every year is not in line with the amount of production each. The increase in crop production is often not balanced with an increase in fertilizer production resulting in fertilizer scarcity which results in crop. One solution that can be done is to use seaweed (Sargassum spp) which can be used as organic. This is because seaweed (Sargassum spp) contains important minerals needed by plants and can increase plant growth and crop The use of seaweed as fertilizer is expected to be an alternative solution to environmental problems because it is safe for soil microbes and Based on this, research has been conducted on the use of liquid fertilizer from seaweed (Sargassum spp) on the growth of shallots (Allium cepa).This study aims to determine the effect of applying liquid fertilizer from seaweed (Sargassum spp) with different concentrations on the growth of shallots (Allium cepa). This research was conducted from November 2022 to January 2023 at the Wire House of the Plant Physiology Laboratory of the Department of Biology, Faculty of Mathematics and Natural Sciences, Padang State This study used a Complete Randomized Design (RAL) with 4 treatments and 6 repeats. The treatment tested in this study was the concentration of liquid organic fertilizer from The data analyzed using ANOVA was followed by DMRT (Duncan's Multple Range Test) at a confidence level of 5%. The results showed that the application of liquid fertilizer from seaweed (Sargassum spp) with different concentrations affected the growth of heigh and dry weight of onion plants (Allium cepa), but did not affect the growth of the number of leaves and wet weight of onion plants (Allium cepa).